TRANSFORMASI DIGITAL DALAM PENYUSUNAN RKA-SKPD: STUDI SLR - Djasuli, Mohammad; Cahyani, Desi Indra; Syamsuddin; RA Nindy Nur Innika P; Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Digital transformation in the public sector has evolved from just an administrative tool to a strategic instrument in adaptive and data-based regional financial management. However, the study of digital transformation in the preparation of the Regional Apparatus Work Unit Work Plan and Budget (RKA-SKPD) still tends to be partial and focuses on technical aspects, without integrating the overall strategic, organizational, and resource readiness dimensions. This research aims to fill this gap through the Systematic Literature Review (SLR) approach. This study analyzes the scientific literature for the period 2018–2026 related to digital transformation, e-budgeting, and regional financial information systems. The results show that digital transformation not only improves efficiency, transparency, and accountability, but also drives a paradigm shift in the budgeting process, from an administrative approach to a data-based and analytics-based approach. In addition, the successful implementation of digital transformation is greatly influenced by the synergy between technology, human resource capacity, and strong institutional commitment. The findings of this study show that most previous studies have not examined the relationship between these three aspects integratively in the context of the preparation of RKA-SKPD. Therefore, this research offers a contribution in the form of a conceptual framework that places digital transformation as an ecosystem that connects technology, governance, and organizational culture. The implications of this research are expected to be a strategic basis for local governments in optimizing budgeting digitalization in a sustainable manner.